Synthesis and Preliminary Anticancer Evaluation of 6-Mercaptopurine –Methotrexate Conjugate as Possible Mutual Prodrug - Al-Darraji, Asmaa S.; H.Mohamed, Mohamed (Iraqi Journal of Pharmaceutical Sciences, 2019)
Small molecules drug conjugate mutual prodrug design (SMDC) composed of folate and lethal agent conjugate, rigidly bonded via hydrophilic bridge and self immolative disulfide bond ; represent new interesting approaches for cancer treatment , the component of SMDC intended for targeting folate receptor , along with greater conservation of component until reaching the target tumor tissue . The designing and synthesis of compound VI and VIII derived from 6-Mercaptopurine (6-MP) and Methotrexate ( MTX) conjugate altogether as mutual prodrugs were processed forward successfully by multistep reaction procedures , and by Thin Layer Chromatography (TLC) for preliminary detection of products and their intermediates, along with their purity. The structures of two final compounds and their intermediates were proclaimed by melting point measurement, infrared spectrometry and ¹HNMR analysis given results greatly correspond with theoretical proposed chemical structure of synthesized compounds. Furthermore, cytotoxic activity evaluation on cell line level had been done for two final compounds against human breast tumor cell (MCF-7) and human ovarian tumor cell (SKO-3) types of cancer cell line and the results were confirmed which show greater cytotoxic tumor activity of two final compounds, while compound VI possess optimal activity proportional with increased number of 6-MP molecules.